Exploring The Anti-Cancer Potential of Triphala: A Study on Leukemia Cell Lines - Vilas Mane, Shivraj; Pal Singh, Ravindra (Journal of Neonatal Surgery, 2025)
Cancer, particularly blood cancers like leukemia, represents a significant public health concern worldwide, with limited treatment options and severe side effects associated with conventional therapies. Traditional medicine, including Ayurvedic formulations, offers a promising alternative for managing these conditions with fewer adverse effects. Triphala, a polyherbal formulation consisting of Emblica officinalis, Terminalia chebula, and Terminalia bellirica, is known for its antioxidant, anti-inflammatory, and immunomodulatory properties. Recent studies suggest that Triphala may exert anti-cancer effects through apoptosis induction, angiogenesis inhibition, and modulation of cancer cell survival pathways. However, its specific effects on blood cancer cell lines have not been extensively studied. The aim of this study was to evaluate the cytotoxic effects of Triphala on human blood cancer cell lines HL-60 (human promyelocytic leukemia) and K562 (chronic myelogenous leukemia). Aqueous of Triphala were prepared and used to treat the cells at concentrations ranging from 25 to 200 μg/ml for 24, 48, and 72 hours. The cytotoxicity was assessed using the MTT assay, and cell viability was measured at 570 nm. The results demonstrated that Triphala exhibited dose- and time-dependent cytotoxicity in both cell lines, with HL-60 cells being more sensitive than K562 cells. The IC₅₀ values for HL-60 and K562 cells were approximately 90 μg/ml and 110 μg/ml, respectively. These findings suggest that Triphala holds significant promise as a therapeutic agent for blood cancers, warranting further investigation into its mechanisms of action, molecular targets, and potential clinical applications